Pengaruh Fraksi Pasir Dalam Campuran Tanah Lempung Terhadap Nilai CBR dan Indeks Plastisitas Untuk Meningkatkan Daya Dukung Tanah Dasar - Lusmeilia Afriani; Yan Juansyah (Rekayasa : Jurnal Ilmiah Fakultas Teknik Universitas Lampung, 2016)
CBR-value is used as an index of soil strength and bearing capacity. This value is broadly used and applied in design of the base and the sub-base material for pavement. Sand –stabilized soils are often used for the construction of these pavement layers and also for embankments. CBR-value is a familiar indicator test used to evaluate the strength of soils for these applications. CBR-test was conducted to characterize the strength and the bearing capacity of the studied soils and their mixtures with sand. CBR-values of the diference soils, compacted at optimum water content, Atterbeg limit are given in this report. All the specimens were prepared using a standard proctor test. The results of the research will be made in the form of a graph on the relationship between the value of CBR to the liquid limit., LL, maximum dry density. The results also will display the graphic relationship between the plasticity index with content of sand fraction and clay fraction. The test results show that the Atterberg limits that a percentage of the original soil and addition of sand. ff (loose soil). The results showed that Relationships LL CBR value and the fraction of sand fraction that the lower the value of LL will increase the value CBRnya. The results showed that the content of the sand can increase the value CBRn. CBR value is highest at 71.11% sand content.